Leukocyte transcriptome indicators of development of infection in kidney transplant recipients. Issue 4 (5th March 2021) - Schaenman, Joanna M.; Rossetti, Maura; Liang, Emily C.; Lum, Erik; Abdalla, Basmah; Bunnapradist, Suphamai; Pham, Phuong Thu; Danovitch, Gabriel; Reed, Elaine F.; Cole, Steve W.
Abstract: After kidney transplantation, infection and death are important clinical complications, especially for the growing numbers of older patients with limited resilience to withstand adverse events. Evaluation of changes in gene expression in immune cells can reveal the underlying mechanisms behind vulnerability to infection. A cohort of 60 kidney transplant recipients was evaluated. Gene expression in peripheral blood mononuclear cells 3 months after kidney transplantation was analyzed to compare differences between patients with infection and those who were infection‐free in the first‐year post‐transplant. Pro‐inflammatory genes such as IL1B, CCL4, and TNF were found to be downregulated in post‐transplant PBMC from patients who developed infection. In contrast, genes involved in metabolism, HLA genes, and transcripts involved in type I interferon innate antiviral responses were found to be upregulated. Promoter‐based bioinformatic analyses implicated increased activity of interferon regulatory factors, erythroid nuclear factor (E2), and CCAAT‐enhancer‐binding protein (C/EBP) in patients who developed infections. Differential patterns of gene expression were observed in patients who developed infection after kidney transplantation, with patterns distinct from changes associated with patient age, suggesting possible mechanisms behind vulnerability to infection. Assessment of gene expression in blood may offer an approach for patient risk stratification and monitoring after transplantation.